Influence of genotype on the quality of sheep leather - Jacinto, Manuel Antônio Chagas; Vargas Junior, Fernando Miranda de; Martins, Charles Ferreira; Pinto, Guilherme dos Santos; Reis, Fernando Alvarenga; Oliveira, Alexandra Rocha de [UNESP] (Sociedade Brasileira de Zootecnia, 2011)
The objective of this study was to evaluate the influence of crossings between sheep breeds on the intrinsic quality of leather. It was used the skins of 36 lambs (18 females and 18 males), resulting from crosses between ewes of a native breed from the Brazilian state of Mato Grosso do Sul and rams of the same native breed as well as the Texel and Santa Inês genetic groups. The animals were raised in confinement until slaughter weight, from 28 to 32 kg. After slaughter, samples were taken from the skins for histological analysis. The skins were tanned with chromium, retanned and greased. It was taken from the leather samples for electromicrographs and for tests for tensile and tear strength (intrinsic quality). Morphological aspects from the skin as well as from the leather help to understand the results found and they evidence that breeds or crossings among breeds interfere in the intrinsic quality of leather and skin of sheep.
Keywords: electromicrograph; photomicrograph; physical-mechanical; skin; tanning